Critical care nurses' communication experiences with patients and families in an intensive care unit: A qualitative study. - Hye Jin Yoo; Oak Bun Lim; Jae Lan Shim (PLoS ONE, 2020)
This study evaluated the communication experiences of critical care nurses while caring for patients in an intensive care unit setting. We have collected qualitative data from 16 critical care nurses working in the intensive care unit of a tertiary hospital in Seoul, Korea, through two focus-group discussions and four in-depth individual interviews. All interviews were recorded and transcribed verbatim, and data were analyzed using the Colaizzi's method. Three themes of nurses' communication experiences were identified: facing unexpected communication difficulties, learning through trial and error, and recognizing communication experiences as being essential for care. Nurses recognized that communication is essential for quality care. Our findings indicate that critical care nurses should continuously aim to improve their existing skills regarding communication with patients and their care givers and acquire new communication skills to aid patient care.